Sosialisasi Dan Pendampingan Sertifikasi Halal Bagi Umkm Di Kota Pekanbaru - Endrianto Ustha; Sitti Rahmah; Nanda Suryadi; Virna Museliza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
There are many aspects that MSMEs in the food industry need to consider, one of which is obtaining halal certification. This certificate, issued by the Halal Product Guarantee Agency (BPJPH), is essential for MSMEs. Moreover, the majority of Indonesia’s population is Muslim and requires assurance that the food products they consume are halal. Halal certification helps boost consumer trust, market share, and business competitiveness. By holding a halal certificate, SME products will be more readily accepted in the market, particularly among Muslim consumers who require halal products to ensure safety when consumed. The objective is to enhance SME operators’ knowledge and awareness regarding the importance of halal certification. The outreach methods include interactive lectures, group discussions, hands-on halal certification registration practice, and individual consultations for SMEs, along with the activity’s target audience. The participants in this community service program are women entrepreneurs in the food and beverage sector in the city of Pekanbaru. The expected outcome of this community service activity is that women entrepreneurs in the food and beverage sector will be able to understand the importance of obtaining halal certification through the Self-Declaration process for food and beverage products, as well as the importance of using ingredients, equipment, and food and beverage processing methods that comply with halal criteria. Keywords: Outreach, Assistance, Halal Certification, UMKM